2019
DOI: 10.1108/yc-12-2018-0922
|View full text |Cite
|
Sign up to set email alerts
|

Understanding online shopping behaviours and purchase intentions amongst millennials

Abstract: Purpose The purpose of this paper is to examine online purchase behaviours amongst young consumers in Australia and the USA. It also aims to develop and test a theoretical framework of young consumers’ online purchase behaviour. Design/methodology/approach Data were collected through online surveys targeting young online shoppers in Australia and the USA. A multi-group structural equation modelling was used to test the proposed structural model and hypotheses. Findings The model shows a good fit with the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 51 publications
4
19
0
7
Order By: Relevance
“…Considering social risk, this result indicates a significant positive relationship with initial trust. This result echoes the work of Dharmesti et al (2021), who found that social motives negatively affect the online purchase intentions of the young generation. One possible explanation is that youths like to experience adventure, so peers' concerns about emerging technologies may not deter YRIs but rather encourage them to try such technologies.…”
Section: Jfrasupporting
confidence: 88%
“…Considering social risk, this result indicates a significant positive relationship with initial trust. This result echoes the work of Dharmesti et al (2021), who found that social motives negatively affect the online purchase intentions of the young generation. One possible explanation is that youths like to experience adventure, so peers' concerns about emerging technologies may not deter YRIs but rather encourage them to try such technologies.…”
Section: Jfrasupporting
confidence: 88%
“…Uses and Gratifications has been also previously used to understand engagement with esports (Lee and Schoenstedt 2011;Bányai et al 2019). In addition, U and G has also been shown to provide a viable means of understanding video game play (Wu, Wang, and Tsai 2010), while Motivation Theory proposes that both purchase decisions and actual purchase behaviour are influenced by both cognitive and affective motivational drivers (McGuire 1976;Dharmesti et al 2019). Experiential factors, including intrinsic and affective motivations (Koo 2009) and attitude (Hsu and Lu 2017) have also been found to be important drivers of game play.…”
Section: Theoretical Framing Of the Studymentioning
confidence: 99%
“…Nevertheless, it is telling that, while technology use varies widely by country, younger people, whether in advanced or emerging economies, are more likely to be digitally connected: to have smartphones, access the internet, and use social media (Pew Research Center, 2019). The specific example of a comparative study of the online shopping behaviours of Australian and American millennials provides further proof of the basic similarity characterizing them as a generation: the unique features attributable to them have been found to influence their shopping practices in a similar way, with only small differences (Dharmesti, Dharmesti, Kuhne, & Thaichon, 2019). Indeed, in a study that sought to establish expressly whether millennials are the same the world over via a comparison of this generational cohort in the USA, Sweden, and New Zealand, they were found to be alike in many ways, most notably for our purposes here on the value dimensions of openness, collaboration/teamwork, and security, although, importantly, they manifested some differences, too, stemming from their cultural upbringing in each country (Schewe et al ., 2013).…”
Section: Background and Contextmentioning
confidence: 99%